Chromium-Catalyzed Asymmetric Dearomatization–Addition Reactions of Halomethyloxazoles and Indoles - Wang, Zheng; Ji, Hongtao; He, Wei-Min; Xiong, Yang; Zhang, Guozhu (Synthesis, 2018)
The asymmetric dearomatization–addition reaction of halomethyloxazoles and halomethylindoles with aldehydes is realized in the presence of a carbazole-based bisoxazoline CrCl2 complex to afford the corresponding enantioenriched, hydroxylated oxazoline and indoline products. The observed excellent chemo-, regio-, diastereo- and enantioselectivities are notable advantages of this protocol. The strategy established in this study is expected to find application in the synthesis of azaheterocycles with biological significance and useful functionalities.
Keywords: asymmetric–dearomatization; chromium catalysis; oxazolines; indolines; azaheterocycles